Impact of Current Malaria Infection and Previous Malaria Exposure on the Clinical Profiles and Outcome of COVID-19 in a High Malaria Transmission Setting - Achan, Jane (Lancet, 2021)
Background: Our understanding of the potential impact of SARS-CoV-2 and malaria co-infection on host susceptibility and pathogenesis remains unclear. We determined the prevalence of malaria and describe the consequences of SARS-CoV-2 and malaria co-infection in a high burden malaria setting. Methods: This was a prospective cohort study of hospitalized Covid-19 patients in Uganda. Malaria diagnosis was done using rapid diagnostic tests, microcopy and molecular methods. Previous P. falciparum exposure was assessed using serologic responses to a panel of P. falciparum antigens using a multiplex bead assay. Additional evaluations included complete blood count, markers of inflammation and serum biochemistries. Findings: Of 597 PCR confirmed Covid-19 cases enrolled between 16th April and 30th October 2020, 500 (84.1%) were male and median age (1QR) was 36 (28-47) years. Overall prevalence of P. falciparum infection was 11.7% (70/597, 95% CI 9.4 to 14.6), with highest prevalence in the 0- 20 years (21.7%, 5/23, 95% CI 8.7-44.8) and > 60 years (19.6%, 9/46, 95% CI 10.2-34.1) age groups. Confusion [5.7% (4/70) vs. 1.5%, (8/527), p=0.04] and vomiting [5.7% (5/70) vs.1.0%, 5/527), p=0.007] were more frequent among patients with P. falciparum infection. Patients with low previous P. falciparum exposure had a higher frequency of severe/critical Covid-19 cases (30.2%, 16/53, p=0.001), a higher burden of comorbidities [hypertension (30.2%, 16/53, p=0.02) and diabetes (22.6%, 12/53, p=0.003)] and more deaths (3.8%, 2/53, p=0.01). Among patients with no comorbidities, those with low previous exposure still had a higher proportion of severe/critical Covid-19 cases (18.2%, 6/53 vs. 2.0%, 1/56, p=0.01) compared to those with high exposure. Interpretation: Prevalence of P. falciparum infection among Covid-19 patients was relatively high. Though Covid-19 patients with P. falciparum infection had a higher frequency of confusion and vomiting, co-infection with malaria did not seem deleterious. Low previous malaria exposure was associated with severe/critical Covid-19 and adverse outcomes. Funding: Funding: Grant from Malaria Consortium, US Declaration of Interest: HA and FN are members of the Mulago Hospital Research and Ethics but did not participate in decisions pertaining this study. All other authors declare no competing interests. Ethical Approval: The study was approved by the Mulago National Referral Hospital Research and Ethics committee and the Uganda National Council for Science and Technology.
: a prospective cohort study
Keywords: Malaria Exposure; Malaria Infection; Malaria transmission; Clinical profiles; COVID-19